Comparative time-course study of aminoacyl- and dipeptidyl-resin hydrolysis - Jubilut, Guita N.; Marchetto, Reinaldo [UNESP]; Cilli, Eduardo Maffud [UNESP]; Oliveira, Eliandre; Miranda, Antonio; Tominaga, Mineko; Nakaie, Clóvis R. (FapUNIFESP (SciELO), 1997)
The classic hydrolysis procedure for quantification of resin-bound aminoacyl and peptidyl groups with 12 N HCl: propionic acid was recvaluated by studying the influence of the nature of the resin and the resin-bound group. Their stability during acid hydrolysis was dependent on the C-terminal amino acid, and the order of acid stability was Phe > Val > Gly. Otherwise, the dipeptides Ala-Gly, Ala-Val, and Ala-Phe displayed enhanced rates of hydrolysis of the resin if compared with their parent aminoacyl groups. Amongthe resins assayed, the order of acid stability was: benzhydrylamine-resin > p-methylbenzhydrylamine-resin ≅4-(oxymethyl)-phenylacetamidomethyl-resin > chloromethyl-copolymer of styrene-1%-divinylbenzene. Important for peptide synthesis method, the findings demonstrate that longer hydrolysis times than previously recommended in the literature (1 h at 130°C and 15 min at 160°C for peptides attached to the chloromethyl-copolymer of styrene-1%-divinylbenzene) are necessary for the quantitative acid-catalyzed cleavage of some resin-bound groups. The observed broad range of hydrolysis time varied from less than 1 h to about 100 h.
Keywords: Acid hydrolysis; Acyl-resin hydrolysis; Amino acid analysis; Peptide hydrolysis; Resin; Solid phase peptide synthesis